Effect of Soaking Time and Temperature on Halo Willimite Crystal Glaze - มีทอง นงลักษณ์; กําลังสง่า พินิตา; ตะเพียนทอง พรจรัส; ไทยทะเล ปาริทัศน์; สืบสวน สุทธิพงษ์; ศรีหล่มสัก สุธรรม (KKU Science Journal, 2014)
Crystal glaze makes beautiful ceramic surfaces. However, it is difficult to fire crystal glaze so that it has same beautiful look every time. This is because there are many factors which affect its appearance. In order to investigate the effects of these factors, firing profile, glaze composition and thickness of glaze were varied. It was found that larger and more beautiful Willimite crystals could be obtained by providing longer soaking time at the crystal growth temperature. Moreover, by alternately increasing and decreasing temperature during the crystal growth firing period, halo crystal glazes can form. Finally, large crystals that form attractive glazes can be obtained by increasing the number of glaze applications. However, these effects also depend upon the glaze composition.